Modified watershed processing with SAR velocities for individual glacier drainage basins on ice sheets - Krieger, Lukas; Floricioiu, Dana (2021)
Individual drainage basins of ice sheets specify the glaciated area that is drained by a single outlet glacier. These catchments are needed to partition mass balance measurements to the single glacier level. Until recently, complete glacier inventories that contain annotated basin information were missing for the Earth's two ice sheets. Here we present a fully traceable methodology to produce catchments applied to the entire Greenland ice sheet. The results have been generated by a modified watershed algorithm which is based on ice flow directions from TanDEM-X elevations and Sentinel-1 velocity measurements.